Micronuclei, nucleoplasmic bridges, and nuclear buds induced in human lymphocytes by the fungicide signum and its active ingredients (boscalid and pyraclostrobin). Issue 7 (22nd June 2012) - Çayır, Akin; Coskun, Munevver; Coskun, Mahmut
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the genotoxic and cytotoxic potential of the Signum fungicide and its active ingredients (boscalid and pyraclostrobin) on human peripheral blood lymphocytes using the cytokinesis‐block micronucleus (CBMN) assay. Micronuclei (MNi), nucleoplasmic bridges (NPBs), nuclear bud (NBUDs) formations, and the cytokinesis‐block proliferation index (CBPI) were evaluated in treated lymphocytes in Go (cells were treated and then kept in culture without stimulation for 24 h) and proliferation phases (cells were treated after 44 h culture in medium containing phytohemagglutinin). MN formation in lymphocytes treated in G0 statistically increased at doses of 2, 6, and 25 μg/mL signum; 0.5 and 2 μg/mL boscalid; and 0.5, 1.5, and 2 μg/mL pyraclostrobin; while NPB formation increased at a dose of 0.25 μg/mL pyraclostrobin. All concentrations of each fungicide did not statistically increase NBUD formation, while the cytotoxicity increased the dependent on concentration in lymphocytes treated in G0. Doses of 0.5, 1, 1.5, and 3 μg/mL signum; 0.5, 1, and 1.5 μg/mL boscalid; and 0.75 μg/mL pyraclostrobin statistically increased the MN formation in proliferating lymphocytes. NPB formation increased in proliferating lymphocytes at doses of 1, 1.5, 2, and 3 μg/mL signum and at a dose of 0.75 μg/mL pyraclostrobin. In addition, a dose of 0.75 μg/mL pyraclostrobin increased NBUD frequencies. Cytotoxicity increased with increasing concentrations of each fungicide. It is concluded that signum, boscalid, and pyraclostrobin may be genotoxic and cytotoxic in vitro human peripheral blood lymphocytes in consideration of each of the two protocols. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 723–732, 2014.